Penerapan Fungsi POAC Pada Upaya Penurunan Angka Stunting Desa Sibalaya Selatan - Fahmi Fahmi (Manajemen Kreatif Jurnal, 2023)
Efforts to reduce stunting rates in Sibalaya Selatan Village are carried out through data collection on stunted children, provision of supplementary food, socialization, and monitoring and evaluation. The POAC function (planning, organizing, actuating, Controling.) method is used to ensure that the activities carried out are planned, coordinated and measurable. Implementation of activities is carried out by involving the community, government, and related institutions. The results of the evaluation show that the implementation of the activity has succeeded in increasing community awareness about the importance of good nutrition for child development and reducing the stunting rate in the village. It is hoped that the results of this report can provide an overview of the implementation of POAC management in handling stunting rates and provide inspiration for other villages to implement similar programs.